2017
DOI: 10.1515/aup-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for Use of Wood in Architecture: The Latvian Case

Abstract: Wood in general is a traditional building material in Northern Europe including Latvia and other Baltic countries, but nowadays it is used less in Latvia than in other EU countries. There are many forests in Latvia and a well-developed timber industry. Latvian society is enthusiastic about eco-materials, and qualified architects and engineers are ready to work with timber structures. However, wood is mainly used for small buildings and residential construction, but minimally in public and multi-apartment build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
4
12
0
Order By: Relevance
“…It was found that compatibility with building codes, availability of technical information, misperceptions about wood or CLT, and cost were the most significant barriers noted by these experts in Europe. Similar results were obtained by Viļuma & Bratuškins (2016) in their study conducted in Latvia which surveyed 73 architects and asked them about barriers preventing the use of wood in construction projects. The most significant barriers in decreasing order of importance were stereotypes, legislation, specialist qualification, lack of knowledge, lack of experience, lack of information, and inaccessible consultancy.…”
Section: Background Researchsupporting
confidence: 81%
See 1 more Smart Citation
“…It was found that compatibility with building codes, availability of technical information, misperceptions about wood or CLT, and cost were the most significant barriers noted by these experts in Europe. Similar results were obtained by Viļuma & Bratuškins (2016) in their study conducted in Latvia which surveyed 73 architects and asked them about barriers preventing the use of wood in construction projects. The most significant barriers in decreasing order of importance were stereotypes, legislation, specialist qualification, lack of knowledge, lack of experience, lack of information, and inaccessible consultancy.…”
Section: Background Researchsupporting
confidence: 81%
“…Architects, who are interested in using renewable materials for their projects, see CLT systems as a great way to mitigate the carbon footprint in construction systems and also as a strategy to increase aesthetic beauty, while decreasing lead times and overall manufacturing and construction costs (Viļuma & Bratuškins 2016). Companies that have participated in CLT construction projects have indicated that these systems can decrease their construction lead times by 25% or more, compared to other materials, impacting overall construction costs (ThinkWood 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, information from municipal stakeholders regarding their perceptions or preferences toward WMC would be useful to unraveling its future potential. Unfortunately, such data are very limited, and not only in the international literature [14,[30][31][32][33][34][35], but in the Finnish context as well. Studies from Finland have focused on topical lenses (e.g., technical innovation, the role of sustainability) as opposed to providing a comprehensive view on general stakeholder attitudes, perceptions, or preferences for WMC [10,[36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The research data consists of three parts. The semi-structured interviews act as a primary source of results (1). The log-utilizing proposals were not awarded in NC.…”
Section: B Datamentioning
confidence: 99%
“…The barriers for using log are mainly similar than the barriers with wood building in general. These include, for example stereotypes [1]. Moreover, the intuition among architects still is that log is better suitable for rural settings than for urban centers [2].…”
Section: Introductionmentioning
confidence: 99%